Virtual currencies in the balance of Islamic jurisprudence and positive laws - Omar, Nessil (International journal of economic perspectives, 2025)
This study examines the positions of both Islamic jurisprudence and positive laws on the circulation of virtual currencies and their use as a medium of commercial exchange. Virtual currencies are one of the most prominent financial innovations of the modern era. These currencies raise complex legal questions related to the extent of state recognition, the controls on their use, consumer protection, and the fight against money laundering and illicit financing. From a legal perspective, these virtual currencies raise numerous questions about their compatibility with the provisions of Islamic law. This study aims to compare Islamic jurisprudence and positive laws on this matter through two axes. The first axis addresses the concept and types of virtual currencies, while the second axis explains the position of Islamic jurisprudence and positive laws on their circulation. The study concludes with the most prominent findings. We will attempt to answer this problem through two axes. The first axis explains the concept and types of virtual currencies, while the second axis addresses the position of Islamic jurisprudence and positive laws on them.